Classroom Teachers' Strategies in Dealing with Dysgraphia - Sri Sekar Ningsih; Novita Novita; Rini Setyowati; Siti Juariah (Aqlamuna: Journal of Educational Studies, 2024)
This study aims to identify and analyze the strategies that have been applied by grade 3 teachers at SDIT Madaris Al-Hasania in dealing with students who experience difficulties in writing, namely dysgraphia. Dysgraphia is a neurological condition that causes students to have difficulty writing, which can hinder the learning process in students. The research method used is qualitative descriptive, with data collection techniques through interviews, observations, and documentation. The results showed that there was one student who experienced dysgraphia with consistent writing difficulties, such as writing backwards and lack of focus when writing. The strategies implemented by grade 3 teachers at SDIT Madaris Al-Hasania include the use of effective demonstration methods in stimulating fine motor skills in students and increasing student involvement in learning activities. In addition, special attention and individualized guidance have also been given to students, as well as involving parents in the learning process to support the progress of students' development at home. This study emphasizes the importance of support from families, especially parents and the surrounding environment, in helping students overcome these writing difficulties. With the application of the right strategies, it is hoped that students who experience dysgraphia can improve their writing skills and confidence in every learning process.